(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2017)
This paper presents unpublished material about two monumental bases, probably made during the Roman Imperial age, discovered in piazza del Duomo and via Mercanti. The circumstance of discovery and the almost totally destruction of the archaeological remains make difficult to establish the real function of these bases, built with similar technique and probably for the same purpose. Until the discovery many theories concerning their function were suggested such as medieval towers, honorary arches, tetrapyla and honorary monuments. Thanks to several comparisons many of these assumptions were excluded, leaving the conclusion that the bases were probably built in different periods on the ancient boundary of the pre-Roman city, perhaps to sustain a group of statues or honorary columns.